TI_GERICHTE 11.2009.88 vom 31. Juli 2012 , Scioglimento della partecipazione agli acquisti: ditta individuale del marito - TI Tribunale d'appello (2012)
Scioglimento della partecipazione agli acquisti: ditta individuale del marito